Biocarbon from spent coffee ground and their sustainable biocomposites with recycled water bottle and bale wrap: A new life for waste plastics and waste food residues for industrial uses. (March 2022) - Gupta, Arvind; Mohanty, Amar K.; Misra, Manjusri
Abstract: The current study investigates the recyclability of water bottles (PET) and bale wrap (LLDPE) blends reinforced with biocarbon, for developing sustainable biocomposites with more than 95% recycled material. The reinforcing agent (biocarbon) has been made by pyrolyzing the waste coffee ground at an elevated temperature. Enhanced interfacial adhesion and reinforcement leads to improvement in the flexural modulus (∼55%) and storage modulus (38%) of the biocomposite with biocarbon obtained by pyrolyzing at 900 °C. The presence of lower particle size and relatively higher modulus of biocarbon (900 °C) in comparison to biocarbon (500 °C) results in resistance in polymer chain movement consequently enhance tensile modulus of biocomposite by 39%. Theoretical calculation of reinforcing efficiency factor (r) and effectiveness coefficient of the reinforcement (C) indicates the homogeneous dispersion of biocarbon in the polymer matrix. Overall, developed biocomposites can be a potential candidate for developing the filaments for 3D printing as well as rigid packaging.